Pengembangan Layanan Baru dan Penggunaan Teknologi dalam Strategi Inovasi pada Masa Pandemi Covid-19 - Farisha, Selfi; Hardisman, Hardisman; Putra, Abdi Setia; Anggina, Yani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the development of new services and the use of technology in innovation strategies at Hospital X during the COVID-19 pandemic. The research method uses a case study approach with interviews, document review, and observation, as well as Focus Group Discussions (FGD). The research results show that health service innovation strategies at Hospital hospital services such as registration, payment transactions, service outreach, or online consultations. Apart from that, increasing the use of e-health or IT, such as telemedicine, drive-thru vaccination, drive-thru PCR/antigen/antibody swabs, MCU on site, and home care, etc. can provide speed and accuracy in service delivery. In conclusion, in the digital era, the pace of change has become very fast. Hospital X applies these strategic, creative, execution and organizational factors in innovation. Keywords: COVID-19, Innovation, Service Development, Strategy, Technology.